2018
DOI: 10.3892/ol.2018.9706
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 suppresses cell invasion by targeting SNAI1 and predicts patient prognosis in glioma

Abstract: Glioma is the most common and rapidly progressive type of malignant primary brain tumor in adults. miR-153 plays a major role in many malignancies; nevertheless, few studies have been conducted on glioma. The aim of the present study was to explore the role of miR-153 and SNAI1 on invasion in glioma. Reverse transcription-quantitative PCR was employed to measure the expression levels of miR-153 and SNAI1 mRNA. Transwell assay was utilized to calculate the capacity of invasion. Luciferase report assay was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…miR-153, as one of the conservative miRNAs, was initially found in seven miRNAs specifically expressed in human and mouse brain tissues. 26 Current studies have confirmed that miR-153 is involved in the development and progression of a variety of malignancies, [27][28][29][30][31][32] such as prostate carcinoma, colorectal cancer, hepatocellular malignancy, non-small-cell lung carcinoma, gastric malignant tumor, glioma and BC. However, its role in various tumors is not exactly identical.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…miR-153, as one of the conservative miRNAs, was initially found in seven miRNAs specifically expressed in human and mouse brain tissues. 26 Current studies have confirmed that miR-153 is involved in the development and progression of a variety of malignancies, [27][28][29][30][31][32] such as prostate carcinoma, colorectal cancer, hepatocellular malignancy, non-small-cell lung carcinoma, gastric malignant tumor, glioma and BC. However, its role in various tumors is not exactly identical.…”
Section: Discussionmentioning
confidence: 94%
“…31 miR-153 inhibits glioma progression by directly regulating SNAI1 and downregulation of miR-153 is related to poor prognosis in glioma sufferers. 32 Therefore, these evidence suggest that the biological behavior of miR-153 seems to have cell and tissue specificity, playing distinct roles in different tumors. With regard to the study of miR-153 in BC, Li et al have reported that miR-153 suppresses EMT of BC via targeting MTDH.…”
Section: Discussionmentioning
confidence: 97%
“…However, in some other cancer types, the expression of miR-153 is decreased, playing a role of tumor suppressor. For example, Zhao et al [12] found that miR-153 was down-regulated in glioma tissues and cells versus paracancerous tissues and normal immortalized gliocyte HEB cells. They verified that SNAI1 was a target of miR-153 and had a negative association with miR-153 detected by luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miR-153 has recently been observed in several common human cancer, while miR-153 serves an oncogene [10,11] or tumor suppressive [12–17] role in different cancer types. Previously, miR-153 has been identified to be overexpressed in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most common form of brain cancer (1), and the prognosis of glioma is relatively poor (2). Glioma cells infiltrate the healthy tissues surrounding the main tumor mass, limiting the survival of patients with glioma (3).…”
Section: Introductionmentioning
confidence: 99%